2022
DOI: 10.1108/jhti-05-2022-0211
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influences of employer branding attributes on turnover intentions of hospitality workforce in the COVID-19 in Vietnam

Abstract: PurposeThis study aims to develop a comprehensive understanding about employer branding dimensions as well as the dimension's possible links with turnover intentions through the lens of existing hospitality employees.Design/methodology/approachA survey was conducted based on a sample of 200 hospitality employees in order to examine relationships between employer branding dimensions and turnover intentions. Structural equation modeling (SEM) was used for data analysis and hypothesis testing.FindingsThe findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 89 publications
0
5
2
Order By: Relevance
“…Accordingly, the non-materialistic factors have more value in attracting potential candidates (Kashyap and Verma, 2018). This might be contradictory to the prior studies that have cited the importance of monetary value to attract and retain employees (Rana and Sharma, 2019; Yousf and Khurshid, 2021; Kar and Nguyen Thi Phuong, 2022). Second, an insignificant effect of work-life balance also contradicts previous studies connoting that though graduates have focused goals and aim to achieve work-life balance (Sharma and Prasad, 2018), they may prioritize career development, healthy working and socially responsible environment over work-family balance.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Accordingly, the non-materialistic factors have more value in attracting potential candidates (Kashyap and Verma, 2018). This might be contradictory to the prior studies that have cited the importance of monetary value to attract and retain employees (Rana and Sharma, 2019; Yousf and Khurshid, 2021; Kar and Nguyen Thi Phuong, 2022). Second, an insignificant effect of work-life balance also contradicts previous studies connoting that though graduates have focused goals and aim to achieve work-life balance (Sharma and Prasad, 2018), they may prioritize career development, healthy working and socially responsible environment over work-family balance.…”
Section: Discussioncontrasting
confidence: 78%
“…Accordingly, the non-materialistic factors have more value in attracting potential candidates (Kashyap and Verma, 2018). This might be contradictory to the prior studies that have cited the importance of monetary value to attract and retain employees (Rana and Sharma, 2019; Yousf and Khurshid, 2021; Kar and Nguyen Thi Phuong, 2022).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…The tourism literature has reported antecedents that affect TI, such as job satisfaction (Chen and Wang, 2019), organizational commitment (Yang, 2008), cynicism (Bufquin, 2020), management trainingmanagement style (Malek et al, 2018), and overworkovertime (Tan et al, 2020). Kar and Nguyen Thi Phuong (2023) also found that employer branding attributes such as economic, social, development, and security values had negative impacts on turnover intentions.…”
Section: Turnover Intentionmentioning
confidence: 99%